Applying crime victims rights' to victims of animal maltreatment - Rosengard, David B. (Animals as crime victims, 2024)
Modern animal protection laws tend to situate animals harmed by criminal cruelty as victims of those self-same crimes - and in some situations has permitted admission to the legal category of crime victims. Applying either (or both) of these victim statuses to animals encourages use of animal-forward jurisprudence, which recognizes the interests of animals as legally cognizable, including them in the interest-weighing process courts routinely engage in. This victim status turn has implications both in the field (e.g., widening the grounds for animals to be removed from danger) and the courtroom (e.g., revealing that society long ago crossed the animal rights Rubicon, which turns out to have very little to do with animals being property, persons, both, or neither). Exploring key court cases and statues illuminates paths forward along this animal victim status route.